Erenumab effectiveness and safety: comparison of real-life data and clinical trial results - Dapkutė , Austėja; Ryliškienė, K. (Neurologijos seminarai, 2021)
Background. Erenumab was the first preventive medication targeted to the pathogenesis of migraine to reach Lithuanian market. Previously, evidence of the safety and efficacy of erenumab was supported only by clinical study results, but more recently, real-life data started to appear.The aim of this review is to compare erenumab clinical trial results with already published real-life data in terms of its effectiveness and safety.Methods. Data search was performed in medical literature and international clinical trial databases. 9 clinical trials and 14 real-life data publications were included in this review.Results. Erenumab significantly reduced monthly migraine, headache, and triptan usage days per month both in clinical trials and in real-life data reports. In real-life settings erenumab effectiveness proved to be even greater than in clinical trials. It was also confirmed that erenumab is an effective treatment for highly resistant chronic migraine. However, adverse event frequency was higher in real-life settings, and the most often observed adverse event was constipation. During long-term trials it was less prominent, therefore, it is hypothesized that constipation reduces with time and is highly dependent on lifestyle and dietary habits. No severe adverse events related to erenumab usage were observed in clinical trials, and in real-life settings, severe adverse events that might be related to erenumab usage were extremely rare. Treatment withdrawal was higher in real-life data reports and it was directly related to study duration. It was often caused by personal patient decision, pregnancy planning, and other non-safety related circumstances.Conclusions. Erenumab effectiveness and safety was proved both by clinical trial results and by real-life data. The latter demonstrated greater erenumab effectiveness in real-life settings, as well as higher adverse event frequency and higher treatment withdrawal rate due to adverse events and unsatisfactory results.
Keywords: erenumab; migraine; frequent episodic migraine; chronic migraine; CGRP; monoclonal antibodies